Gambaran Pola Luka dan Prevalensi Kasus Kecelakaan Lalu Lintas di Bagian Ilmu Kedokteran Forensik dan Medikolegal RSUP Prof. Dr. R. D. Kandou Manado Tahun 2022-2023 - Tulung, Margaretha A.; Kristanto, Erwin G.; Tomuka, Djemi (Medical Scope Journal, 2025)
Abstract: Traffic accidents have become one of the health problems causing various material and non-material losses. Victims of traffic accidents can suffer from minor injuries to potentially fatal ones. Patient data on traffic accident cases, including injury patterns, plays a significant role for medical institutions, law enforcement, and the community. These injury patterns may vary among different regions due to various factors. This study aimed to determine the pattern of wounds and the prevalence of traffic accident cases in the Department of Forensic Medicine and Medicolegal at Prof. Dr. R. D. Kandou Hospital Manado in the years 2022-2023. This was a descriptive and retrospective study, using secondary data from Visum et Repertum (VeR) reports of deceased victims due to traffic accident. The results showed that the total number of victims was 36 cases, with 28 victims meeting the inclusion-exclusion criteria. Throughout the years 2022-2023, the highest number of cases occurred in March, with a total of six fatalities. The majority of victims were male, and the most common age group was 17-25 years old (28.57%). The most frequently type of injury was abrasion (54.7%), primarily located on the head and face. The majority of victims were drivers (28.5%), with motorcycles being the most commonly involved vehicles. In conclusion, the majority of cases were male, age group 17-25 years, had abrasion primary located on the head and face, and roled as motorcycle drivers. Keywords: traffic accident; pattern of wounds   Abstrak: Kecelakaan lalu lintas (KLL) menjadi salah satu penyebab masalah kesehatan yang menyebabkan berbagai kerugian material dan non material. Korban KLL dapat mengalami cedera ringan hingga berpotensi menyebabkan kematian. Keberadaan data pasien kasus kecelakaan lalu lintas berupa karakteristik dan gambaran pola luka, memiliki peran signifikan bagi instansi medis, aparat hukum, dan masyarakat. Gambaran pola luka dapat mengalami perbedaan antara korban kecelakaan lalu lintas di suatu daerah dengan daerah yang lain karena berbagai faktor. Penelitian ini bertujuan untuk mengetahui gambaran pola luka dan prevalensi kasus KLL di Bagian Ilmu Kedokteran Forensik dan Medikolegal RSUP Prof. Dr. R. D. Kandou Manado pada tahun 2022-2023. Jenis penelitian ialah deskriptif retrospektif, menggunakan data sekunder dari Visum et Repertum (VeR) korban meninggal dari kasus KLL. Hasil penelitian mendapatkan bahwa jumlah keseluruhan korban sebanyak 36 kasus dengan 28 korban memenuhi kriteria inklusi dan eksklusi. Sepanjang tahun 2022-2023 kasus terbanyak terjadi di bulan Maret dengan total enam korban meninggal. Korban terbanyak berjenis kelamin laki-laki, dan usia pada kelompok 17-25 tahun (28,57%). Jenis luka terbanyak berupa luka lecet (54,7%), dengan lokasi tersering pada bagian kepala dan wajah. Jenis peran korban terbanyak sebagai pengemudi (28,5%) dengan kendaraan paling banyak terlibat berupa sepeda motor (32,14%). Kata kunci: kecelakaan lalu lintas; pola luka